2014
DOI: 10.5430/ijfr.v5n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Testing International Momentum Strategies between Chinese and Australian Financial Markets

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…The two indices seem to track each other closely, implying that they may be economically linked with each other. Previous studies have demonstrated that the Chinese and Australian markets are linked through trade, with Australian exports of metals, coal and minerals benefitting both countries (for example Abraham, 2013a;and Abraham, 2013b). The Efficient Market Hypothesis (EMH) is based on the following assumptions (Soares et al, 2005 andBurghardt, 2010);…”
Section: Introductionmentioning
confidence: 99%
“…The two indices seem to track each other closely, implying that they may be economically linked with each other. Previous studies have demonstrated that the Chinese and Australian markets are linked through trade, with Australian exports of metals, coal and minerals benefitting both countries (for example Abraham, 2013a;and Abraham, 2013b). The Efficient Market Hypothesis (EMH) is based on the following assumptions (Soares et al, 2005 andBurghardt, 2010);…”
Section: Introductionmentioning
confidence: 99%